Transoceanic Migrations (1998-2009): The (Re)Construction of Contemporary Italianness among Italo-Descendants from Argentina and Brazil - Mélanie Fusaro; Petterson Molina Vale (Diasporas: Circulations, Migrations, Histoire)
For nearly a century the Italian «great emigration » (1860-1970) drove millions of migrants to South America, in particular to Argentina and Brazil. According to the Italian legislation, their descendants are still entitled to the Italian nationality iure sanguinis. On which «Italianness» does this legal recognition lie? How was the identity of these «oriundi» shaped and passed on throughout the generations?